Public Broadcasting and Topic Diversity in The Netherlands: Mentions of Public Broadcasters’ Programming in Newspapers as Indicators of Pluralism - Veerbeek, Joris; van Es, Karin; Müller, Eggo (Javnost-The Public, 2022)
Following debates on media pluralism and decentralised public service media, this article discusses the contribution of Dutch public broadcasters to pluralism. While the Dutch system operates under the assumption that external pluralism of broadcasting associations contributes to diversity, here we empirically explored this relation with respect to topics within societal discourse. We argue that mentions of public broadcasters’ programming in newspapers can function as indicators of diversity. As such, we traced mentions of all television and radio programmes by eleven Dutch public broadcast associations in a collection of 263,476 Dutch newspaper articles published during the 2017–2018 TV and radio season. Employing Latent Dirichlet Allocation topic modelling, we thematically contextualised those mentions, which then allowed us to map the breadth of topics associated with programming by different public broadcast associations as well as the extent to which individual public broadcasting associations play a distinct role within a characteristic set of topics. The results of our exploratory analyses support the idea that the external pluralism of the Dutch system produces diversity in alignment with the intentions of the distributed system.